Desarrollo de la competencia digital del alumnado desde el Marco de Referencia de la Competencia Digital en los docentes de la Unidad Educativa Marieta de Veintimilla, de la ciudad de Loja, sección vespertina, año lectivo 2022-2023. - Espinosa Alvarez-, Anderson Danilo (2023)
Digital skills are technical and cognitive skills necessary to face professional challenges and throughout life. In teaching, this skill is established as the ability to promote the acquisition of knowledge, using a set of strategies supported by various materials, digital equipment in search of generating a good level of learning in students. That is why the Common Framework for Teaching Digital Competence provides a guide for the diagnosis and improvement of digital competences, which is made up of 6 areas. This research refers to Area 6 Development of students' digital competence, which It is related to the teaching ability to encourage students to use technology in the acquisition of knowledge through various materials and resources that strengthen the teaching-learning processes, the methodology used is a quantitative approach of a descriptive exploratory type, the population analyzed is 20 teachers who responded to a survey prepared especially for this purpose, the study area is the Marieta de Veintimilla Educational Unit in the city of Loja, evening section, school year 2022-2023. The results establish that the teachers of the aforementioned educational institution are mostly in stage B experience, they have a high degree of autonomy when using technologies in their practice, they carry out an adequate management of tools, theological resources that contribute to strengthen their academic work, they can sometimes help other teachers. Keywords: Digital competence, student competence, teaching and learning.